Penurunan Daya Saing Global Indonesia : Pembangunan Infrastruktur Yang Kurang Adaptif Terhadap Perkembangan Isu Cybercrime - Miranda Putri Sembiring (Journal of International Relations Diponegoro, 2022)
ABSTRACTIn October 2019, Indonesia's Global Competitiveness Index decreased 5 places from the previous year. This decline occurred in the midst of massive infrastructure development carried out during the leadership of President Joko Widodo in the first period. The pillar that experienced the highest decline was the pillar of information and communication technology adoption. This study aims to explain why the infrastructure development carried out is less adaptive to issues regarding the development of information and communication technology, so that the indications are that Indonesia is rife with cybercrime cases. The framework used in this research is the hyperglobalist theory and the concept of cybercrime. Hyperglobalist theory is used to analyze the adaptation process of the Indonesian government to industry 4. 0 and the concept of cybercrime is used to analyze the development of cybercrime cases. This study uses a qualitative research method with the type of explanatory research, data obtained through literature study. This research shows that the government is less adaptive to the development of industry 4.0, so that infrastructure development experiences dislocation. The government does not see aspects of the development of information and communication technology at this time, so that cybercrime cases in Indonesia are increasing every year. so that infrastructure development is dislocated. The government does not see aspects of the development of information and communication technology at this time, so that cybercrime cases in Indonesia are increasing every year. so that infrastructure development is dislocated. The government does not see aspects of the development of information and communication technology at this time, so that cybercrime cases in Indonesia are increasing every year.